Pengaruh Model Pembelajaran Berbasis Masalah pada Kemampuan Literasi Ilmiah Siswa dalam Materi Transfer Panas Kelas V di Sekolah Dasar - Khilda Audina; Arie Widya Murni; Novaria Lailatul Jannah; Hikmah Luqiyah Kartikasari (Universitas Muhammadiyah Gresik, 2024)
Thesis This aim For know influence of learning models based problem to ability literacy participant educate on the material displacement heat fifth grade school base . As for the background study This based on results interviews and observations carried out , where ability literacy science participant still studying in class V spelled out low as well as lack of understanding teacher towards various various learning models . Study This carried out at SDN Banjarkemantren 2 in the even semester year 2022/2023 teachings . Method research used _ is Pre Experimental Design with One Group Pretest-Posttest Design type . Sample in study is participant educate VA class totaling 31 participants educate . Instruments used _ form instrument test form question choice double as well as sheet observation teacher and participant activities students , data obtained from test choice double and observation related with ability literacy science . Data analysis used the normality test and t-test. Analysis results show that the data is normally distributed because sig value . > 0.05 and in the t- test with using paired sample t-test results sig value <0.05 at level significance 5% then can it is concluded that h0 is rejected and ha is accepted . This matter show that application of learning models based problem give influence to ability literacy science participant educate on the material displacement heat in class V school base